ANALISIS TERHADAP TINDAK PIDANA PROSTITUSI DIHUBUNGKAN DENGAN ETIKA MORAL SERTA UPAYA PENANGGULANGAN DI KAWASAN CISARUA KAMPUNG ARAB (Jurnal Hukum Mimbar Justitia, 2016)
Prostitution’s phenomenon is one of criminality forms that is very difficult to overcome and this criminality type is widely supported by economic factors in the environment, until now, prostitution cannot be stopped, as well as a treatment to sexual morality, domestic life, health, women’s welfare. One of the problems is because the number of tourists from the Middle East came and went to Kampung Arab, the area of Puncak, Bogor regency particularly. The practical sexual transaction not only experiencing by the prostitutes from Bogor and Cianjur (PSK Domestic) but also between Arabic tourists and Moroccos, what we called Maghribi. Therefore, the government should be more active in seeking solutions to this problem, such as eradicating prostitution bravely in brothels. As the time goes by, Indonesian culture will be eroded from that area and the most worrying is the case of prostitution will multiply as social issues related to moral ethics nationally.Keywords: Prostitution, Moral Ethics and Prevention of Prostitution.